The Effect of Liquidity, Sales Growth and Firm Size on Financial Distress in Manufacturing Companies in Various Industrial Sectors Listed on the Indonesian Stock Exchange for the 2020 - 2022 Period - Lidia Alvionika Nadapdap; Shadrina Hazmi (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This research aims to understand, describe and analyze the influence of liquidity, sales growth and firm size on financial distress in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange for the period 2020 - 2022. Financial distress is a condition of financial difficulty where the company is unable to pay off its debts. and its obligations and occurred before the company went bankrupt. The research method used in this research is logistic regression. The data used is secondary data in the form of financial reports of manufacturing companies in various industrial sectors and the total sample obtained was 43 companies. Data collection methods use documentation techniques and library studies. The research results show that liquidity has a negative effect on financial distress, sales growth has a negative effect on financial distress and firm size has a negative effect on financial distress.